(untitled) (Journal of the Sociology and Theory of Religion, 2018)
The principle of this work is, "rather than reaping certainties, today we must sow doubts", that help to become aware of the world in which we live: a diverse, complex and voluble social reality, which is interconnected globally, although it operates locally , both in a tangible and virtual plane. Many of the western societies have been classified as risky, liquid, diffuse, etc., looking like ultramodern Babels, whose norms and institutions coexist, not without some degree of confusion and latent tension (some in extinction, others transplanted, some syncretized, enough hybridized, and the rest are emerging). Such is the level of dynamism of the current social reality (cohabitating the traditional with the modern and the utopian, plus the centrifugal forces and social factors with the centripetals, etc.), which calls for a revision of available social guides and maps after the globalization and all its crises.